MENINGKATKAN EFEKTIFITAS PEMBELAJARAN MELALUI SUPERVISI KLINIS KINERJA GURU SEKOLAH DASAR NEGERI 013 RAMBAH HILIR - Andriful Andriful (STKIP Rokania Pasir Pangaraian, 2018)
The purpose of this study is to improve the performance of teachers in order to devote time and energy to effective learning. Improve the ability to solve problems in learning through clinical supervision. The results of the description analysis reveal, in the first cycle (one) the level of teacher performance on learning effectiveness has shown an increase compared to the initial conditions. But the results achieved in cycle I did not make the researcher feel satisfied because it was not optimal. Therefore the researcher continued in the second cycle by first making improvements to the weaknesses found in cycle I. In the implementation of the second cycle of action there was a significant increase in the effectiveness of learning